Edification Dictums in the Language Consciousness of the Kazakh Ethnos - Галина Абрамова; Наталія Дмитрюк (Психолінгвістика, 2021)
Introduction. Objective: linguacultural analysis of the edification words, collected in a free associative experiment (FAE) and published in the “Kazakh Associative Dictionary”.